1999
DOI: 10.1016/s0375-9474(99)85080-5
|View full text |Cite
|
Sign up to set email alerts
|

Baryonic contributions to e+e− yields in a hydrodynamic model of Pb+Au collisions at the SPS

Abstract: We analyze e + e − yields from matter containing baryons in addition to mesons using a hydrodynamic approach to describe Pb+Au collisions at 158 A GeV/c. We use two distinctly different e + e − production rates to provide contrast. Although the presence of baryons leads to significant enhancement of e + e − emission relative to that from mesonsonly matter, the calculated results fall below the data in the range 400 < M e + e − /MeV < 600. The calculated results are, however, only 1.3-1.5 standard deviations be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is worthwhile to point out that, during the dense stages of evolution in a heavy-ion collision, the assumption of local thermal equilibrium among the constituents of matter has been gainfully employed to understand photon and dilepton emission. Calculations in the CERN SPS regime have shown that a fair agreement exists between theory and experiment [25,26,28]. In the context of charge fluctuations the equilibrium assumption is supported by the estimates of ∆y diff presented in Ref.…”
Section: B Relation To Other Workmentioning
confidence: 90%
See 1 more Smart Citation
“…It is worthwhile to point out that, during the dense stages of evolution in a heavy-ion collision, the assumption of local thermal equilibrium among the constituents of matter has been gainfully employed to understand photon and dilepton emission. Calculations in the CERN SPS regime have shown that a fair agreement exists between theory and experiment [25,26,28]. In the context of charge fluctuations the equilibrium assumption is supported by the estimates of ∆y diff presented in Ref.…”
Section: B Relation To Other Workmentioning
confidence: 90%
“…Direct photons and dileptons, due to their negligible final state interaction in a heavy-ion collision, have long been recognized as sensitive probes of the physical state of strongly interacting matter. We are thus led to the following natural question: To the extent that electromagnetic observables at the CERN-SPS have been adequately described through a combination of hadronic and partonic approaches [25,26,28] (see [21] for a review), what are the implications of dilepton and photon spectra to be measured at RHIC and LHC on charge fluctuations of hadrons and partons during the dense stages of evolution? The answer to this question hinges critically on the outcome of upcoming measurements and on the ability of theory to model the complex evolution of the system created in a heavy-ion collision.…”
Section: Connections To Heavy-ion Experimentsmentioning
confidence: 99%